She-Chuang-Si-Wu-Tang Alleviates Inflammation and Itching Symptoms in a Psoriasis Mouse Model by Regulating the Th17/IL-17 Axis via the STAT3/MAPK Pathways [Corrigendum] - Chen W; Liang J; He S; Liang Q; Tian W; Lu A; Li D; Huang Z; Wu G (Dove Medical Press, 2024)
Chen W, Liang J, He S, et al. J Inflamm Res. 2024;17:5957–5975. The authors have advised that Table 2 on page 5962 is incorrect. Specifically, the primers were mistakenly labeled as the five herbal components of She-Chuang-Si-Wu-Tang, when they should have been listed as cytokine genes. The correct table is as follows. Table 2 Primer Sequences for Quantitative Reverse Transcription Polymerase Chain Reaction The authors apologize for the error.